Sosialisasi Ekonomi Syariah Melalui Majelis Taklim Tanwirul Qulub Sebagai Upaya Pemberdayaan Ekonomi Umat Desa Padanglampe - Siti Samsuduha; Andi Hasriani (Lembaga Pengabdian kepada Masyarakat Universitas Muslim Indonesia, 2026)
This community service activity is motivated by the community's lack of in-depth understanding of basic concepts of Islamic economics, such as the prohibition of usury, valid sale and purchase contracts, or principles of justice in transactions. This service aims to improve the understanding of the congregation of the Majelis Taklim Tanwirul Qulub regarding the principles of Islamic economics, which are the foundation for daily muamalah activities. The program is implemented thru the delivery of material, interactive discussions, and the presentation of case studies related to Sharia transaction practices. Based on the evaluation results, there was an increase in participants' knowledge about the concept of usury, various types of muamalah contracts, and the application of Islamic finance in the lives of Muslim families. This program is recommended for further development thru advanced training, such as Sharia-based family financial management training.